OBRAZ KOBIETY W TWÓRCZOŚCI ŚPIEWANEJ OKRESU STAROPOLSKIEGO - Jabłońska, Anna (In Gremium. Studies in History, Culture and Politics, 2012)
THE IMAGE OF WOMEN IN OLD POLISH SONGS This article covers the period from the Middle Ages to the Partitions of Poland. It attempts at presenting the different incarnations and roles of women as well as the topoi, archetypes and stereotypes found in song lyrics understood as literary-musical works. One of the most emphasized archetypes is one of a woman-mother. It originates from Mary, the mother of Jesus, an advocate and mediator, the ideal of beauty and women’s character who also shows very human emotions. As it is said in soldier and knight songs, she is also referred to as the guardian of Poland, who helps to defeat enemies. This type of works additionally shows the topos of waiting, longing and suffering women: soldiers’ mothers, sisters and lovers. It also includes descriptions of cruelties of war affecting women and the suffering of mothers losing their children. However, it also shows girls who willingly enjoy themselves with soldiers. Old Polish songs also include an archetype and anti-archetype of a queen, of the ideal wife and her opposite, the so-called “baba”. Also, various views on marriage are presented. In the cases of girls, beloved ones and lovers, the ideal of beauty is presented and different descriptions of physical and platonic love are given. Music was a very important medium and spreading religious rules was one of its roles. From the perspective of music the analyzed works are divided into a) connected with the Church (liturgical and para-liturgical) usually based on chorales, b) secular, mostly from modern times. They represent various levels, origin and character. Some of them were probably only performed in the circles of higher musical culture, however, most of them are songs which could have been performed anywhere by anyone. They have often been popular in many different circles until the present.